SISTEM PENDUKUNG KEPUTUSAN PEMBERIAN BEASISWA PADA MAHASISWA FAKULTAS ILMU TARBIYAH DAN KEGURUAN IAIN JAMBI MENGGUNAKAN METODE PROFILE MATCHING - Lucy Simorangkir (JURNAL AKADEMIKA)
Scholarship is a gift in the form of financial assistance given to individuals, which is intended to be used for the continuation of education pursued. Scholarship is a program of education in all schools and universities both public and private. Similarly, the Faculty of Science and Teaching Tarbiyah State Islamic Institute of Jambi in terms of scholarships are still having trouble because of the criteria used in determi ning the student is more appropriate for the scholarship. This research aims to develop a decision support system providing scholarships to students so that more minimize error correction candidate assessment in receipt of scholarships in order to obtain the assessment process more precise and accurate. This system is built using Borland Delphi 7.0. Input requirement is the student data, student alternative value, the final value of the student and the student's ranking results. If the needs of the process in the form of student data. The need for the output of student data report and report student rankings. The method used in this research is the method Profile Matching. This method outlines a process to compare the actual data values from a profile that will be judged by the value of the expected profile, so that can know the difference competence (also called gap). The results showed that the Decision Support System Profile Matching method can be used as a tool for the faculty in determining a student e ligible to receive a scholarship.